Desmoplastic melanoma may mimic a cutaneous peripheral nerve sheath tumor: Report of 3 challenging cases. (11th May 2017) - Machado, Isidro; Llombart, Beatriz; Cruz, Julia; Traves, Víctor; Requena, Celia; Nagore, Eduardo; Parafioriti, Antonina; Monteagudo, Carlos; Llombart‐Bosch, Antonio
Abstract : Desmoplastic melanoma (DM) and cutaneous malignant peripheral nerve sheath tumors (MPNST) reveal histological and immunohistochemical similarities, including S100 positivity and negative staining for conventional melanocytic markers. We present 3 cases of cutaneous S100‐positive spindle cell tumors in elderly patients, in which first findings led to initial misdiagnoses as cutaneous MPNST and benign peripheral sheath nerve tumor (neurofibroma). The identification of adjacent atypical melanocytic hyperplasia in the overlying skin along with tumor cell proliferation, also in the superficial dermis, the neurotropic component and the absence of any relationship between the tumor and a major nerve, pre‐existing neural benign tumor or the existence of stigmata suggestive of neurofibromatosis raised consideration of a DM. Careful attention should be paid to the presence of a firm dermal nodule and atypical scar lesions especially in sun‐exposed areas (mainly head and neck region) in elderly patients associated with S100‐positive spindle cell proliferation, solar elastosis and adjacent atypical melanocytic proliferation. In such cases, the possibility of a DM should be excluded with caution, especially if the tumor reveals a paucicellular morphology resembling various non‐melanocytic neoplasms including malignant or benign peripheral sheath nerve tumors.